Measuring Cadmium (Cd) in Nile Tilapie (Oreochromis niloticus) from Lake Rawa Taliwang - Mulyati, Suci; Khairuddin, Khairuddin; Yamin, M. (Jurnal Biologi Tropis, 2025)
Taliwang Swamp Lake is a freshwater ecosystem under pressure from anthropogenic activities, including illegal mining, which has the potential to increase heavy metal contamination. This study aimed to measure Cd concentrations in tilapia in Taliwang Swamp Lake and assess their suitability for consumption based on BPOM standards. Data were analyzed using the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) method. The results showed that Cd in tilapia ranged from 0.024 to 0.027 mg/kg, with an average of 0.0255 mg/kg, which is still below the maximum threshold of 0.30 mg/kg. Environmental parameters such as temperature (30oC), pH (7.7-7.8), and salinity (10 ppt) were within the ideal range for aquatic life and did not indicate extreme conditions that could increase Cd bioaccumulation. Visual observation of the fish flesh also showed normal color and texture with no indication of tissue damage due to heavy metal exposure. Overall, tilapia from Lake Rawa Taliwang is still safe for consumption, although regular monitoring is still needed to prevent the risk of long-term Cd exposure.